The peaceful stillness of the silent mind : Buddhism, mind and meditation - Yeshe, Lama.; Ribush, Nicholas (Boston : Lama Yeshe Wisdom Archive, 2010)
Lama Yeshe on Buddhism:"Buddhism is not just about one or two small things; it is not some tiny philosophy. Lord Buddha explained the nature of every single phenomenon in the universe."On Mind:"At certain times, a silent mind is very important, but 'silent' does not mean closed. The silent mind is an alert, awakened mind; a mind seeking the nature of reality."On Meditation:"Meditation is the right medicine for the uncontrolled, undisciplined mind. Meditation is the way to perfect satisfaction. The uncontrolled mind is by nature sick; dissatisfaction is a form of mental illness. What's the right antidote to that? It's knowledge-wisdom; understanding the nature of psychological phenomena; knowing how the internal world functions."This book is made possible by kind supporters of the Archive who, like you, appreciate how we make these teachings available in so many ways, including in our website for instant reading, listening or downloading, and as multimedia, printed and ebooks. Our website offers immediate access to thousands of pages of teachings and hundreds of audio recordings by some of the greatest lamas of our time. Our photo gallery and our ever-popular books are also freely accessible there. Please help us increase our efforts to spread the Dharma for the happiness and benefit of all beings. You can find out more about becoming a supporter of the Archive and see all we have to offer by visiting our website.Thank you so much, and please enjoy this book.
Keywords: Buddhism -- Psychology; Self-perception.; Meditation -- Buddhism; Mind and body -- Religious aspects -- Buddhism